Sulfate-Reducing Bacteria as an Effective Tool for Sustainable Acid Mine Bioremediation - Ayangbenro, Ayansina S.; Olanrewaju, Oluwaseyi S.; Babalola, Olubukola O. (Frontiers in Microbiology, 2018)
Mining industries produce vast waste streams that pose severe environmental pollution challenge. Conventional techniques of treatment are usually inefficient and unsustainable. Biological technique employing the use of microorganisms is a competitive alternative to treat mine wastes and recover toxic heavy metals. Microorganisms are used to detoxify, extract or sequester pollutants from mine waste. Sulfate-reducing microorganisms play a vital role in the control and treatment of mine waste, generating alkalinity and neutralizing the acidic waste. The design of engineered sulfate-reducing bacteria (SRB) consortia will be an effective tool in optimizing degradation of acid mine tailings waste in industrial processes. The understanding of the complex functions of SRB consortia vis-à-vis the metabolic and physiological properties in industrial applications and their roles in interspecies interactions are discussed.